The importance of interlanguage in language teaching: an analysis of its development in l2 learners - Saverio Barone (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The presented research introduces the concept of interlanguage, a key term in the study of second language (L2) acquisition, with particular reference to the teaching of Italian as an L2 to Eastern Slavic speakers, especially Russian native speakers. The concept of interlanguage represented an important theoretical innovation in applied linguistics and has had significant implications for the development of teaching methodologies in the context of language learning. Interlanguage is defined as a dynamic linguistic system that evolves during the process of acquiring a second language. This system consists of linguistic rules that do not fully belong to either the learner’s native language (L1) or the target language (L2) but instead form an «intermediate language». In other words, interlanguage is a transitional and mutable state that reflects the learner’s incomplete linguistic competence in L2. This intermediate system is characterized by its own rules, which the learner develops through processes of generalization, conscious and unconscious learning, and also through errors. One of the crucial aspects of interlanguage, as discussed in the article, is the phenomenon of «fossilization». This term refers to the process by which some erroneous linguistic structures become stable and permanent in the learner’s linguistic system, despite continued exposure to the L2 and attempts at correction. Fossilization represents one of the main challenges in the process of acquiring a second language, as it hinders progress towards complete and fluent competence in the target language. The study also highlights the variability of interlanguage, meaning the learner’s ability to use different linguistic forms in various contexts. This phenomenon reflects the complexity of the acquisition process, where L2 learning is not linear and can vary significantly depending on factors such as the communicative context, motivation, linguistic input, and the learner’s metalinguistic awareness. Another key theme addressed is the importance of feedback in the learning process. Corrective feedback, which can be explicit or implicit, plays a fundamental role in helping learners recognize and correct their errors, thereby preventing fossilization. However, the quality of the feedback and the way it is provided are crucial: well-calibrated feedback can foster more effective learning, while inadequate or excessive feedback may generate anxiety or confusion, slowing down the acquisition process. The research focuses particularly on the difficulties that Russian-speaking learners encounter when learning Italian. The phonological and grammatical differences between Russian and Italian can lead to frequent errors. For example, the use of articles in Italian, which do not exist in Russian, represents a significant challenge for Russian speakers, as does the conjugation of verbs in Italian tenses, which differ greatly from the Russian verbal system. These errors are not random but arise from the intermediate interlanguage system that learners develop. Understanding these systematic errors and their connection to the learner’s L1 allows teachers to intervene more precisely and effectively. Finally, the research discusses the importance of adopting specific teaching strategies to prevent fossilization and promote L2 learning. Among these, communicative activities that provide rich and diverse input, as well as targeted feedback, play a crucial role in correcting errors without undermining the learner’s motivation. Therefore, teachers must be able to adapt to the learner’s interlanguage system and offer appropriate support, taking into account the specific difficulties related to their L1. Only through a flexible and aware approach can errors be prevented from becoming ingrained in the learner’s linguistic system, allowing for continuous progress towards linguistic competence in L2. In summary, the research emphasizes how recognizing interlanguage and its characteristics, such as fossilization, variability, and the importance of feedback, is fundamental for effective foreign language teaching. Specifically, understanding the phonological and grammatical difficulties faced by Russian-speaking learners of Italian can guide the development of more appropriate and personalized pedagogical strategies, improving teaching effectiveness and fostering greater mastery of L2.